2014
DOI: 10.1016/j.niox.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the HNO and NO donating properties of alicyclic amine diazeniumdiolates

Abstract: Nitroxyl (HNO) donors have been shown to elicit a variety of pharmacological responses, ranging from tumoricidal effects to treatment of heart failure. Isopropylamine-based diazeniumdiolates have been shown to produce HNO on decomposition under physiological conditions. Herein, we report the synthesis and HNO release profiles of primary alicyclic amine-based diazeniumdiolates. These compounds extend the range of known diazeniumdiolate-based HNO donors. Acetoxymethyl ester-protected diazeniumdiolates were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Commonly used donors include Angeli’s salt (Na 2 N 2 O 3 ) [241, 288], Piloty’s acid (C 6 H 5 SO 2 NHOH) and derivatives [289, 290], acyl nitroso compounds [291293], acyloxy nitroso compounds [294296] and primary amine based diazeniumdiolates [RNH-N(O)=NO − ] [297, 298]. Among these donor classes, Angeli’s salt is the most prevalent donor used for chemical and biological studies.…”
Section: The Chemical Biology Of Hnomentioning
confidence: 99%
“…Commonly used donors include Angeli’s salt (Na 2 N 2 O 3 ) [241, 288], Piloty’s acid (C 6 H 5 SO 2 NHOH) and derivatives [289, 290], acyl nitroso compounds [291293], acyloxy nitroso compounds [294296] and primary amine based diazeniumdiolates [RNH-N(O)=NO − ] [297, 298]. Among these donor classes, Angeli’s salt is the most prevalent donor used for chemical and biological studies.…”
Section: The Chemical Biology Of Hnomentioning
confidence: 99%
“…77 A group of cyclic primary amine-based diazeniumdiolates (for example, AcOM-CPA/NO, Figure 9) release HNO with a wide-range of half-lives and hold promise in cancer cell targeting. 78 …”
Section: Advances In Hno Sourcesmentioning
confidence: 99%
“…It has also been suggested that HNO donors may represent a new class of inodilators for treatment of heart failure (Favaloro & Kemp‐Harper, ; Feelisch, ; Kemp‐Harper, Horowitz, & Ritchie, ; Paolocci et al, ). In addition to the cardiovascular effects observed, HNO has shown initial promise in the realm of cancer therapy (Bharadwaj et al, ; Norris et al, ).…”
Section: Introductionmentioning
confidence: 99%